Feedback from massive stars at low metallicities: MUSE observations of N44 and N180 in the Large Magellanic Cloud - McLeod, Anna F.; Kruijssen, Diederik; Pellegrini, Eric William (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present MUSE integral field data of two H ii region complexes in the Large Magellanic Cloud: N44 and N180. Both regions consist of a main superbub
Advance access publication 2018 October 5
Gesehen am 03.06.2019